Rock My World: Rewind to a Better Transition to Remote Learning - Garland, Michelle E.; Violanti, Michelle T. (Frontiers in Communication, 2021)
Students and faculty alike found themselves in tumultuous times as they made the transition from face-to-face to remote learning. As faculty and administrators worked hard to overcommunicate with students in the hopes of keeping them engaged and focused on their academic pursuits, students found their attentions split among school, the Covid-19 health pandemic, and paying bills as many lost their employment. In some cases, the overcommunication led to students ignoring messages as they were completely overwhelmed; at the same time, some students found themselves reverting back to looking for the days of someone telling them what to do every minute of the day. Because faculty, and administrators, were not well prepared to handle the situation, an unevenness in how faculty communicated with students occurred. That is, some faculty withdrew in the same way that students did, and the term essentially ended with students turning in remaining assignments even though no further instruction occurred. Other faculty tried to move their face-to-face class online without taking into consideration the differences between these two channels. Still others tried to create an online course as they went from week to week. The inconsistencies across classes combined with the additional stress students were already experiencing became a recipe for exactly what the administration was trying to avoid—unsuccessful completion of courses and/or students unprepared for the courses that would come after the ones in which they were enrolled that term. The purpose of this study is to examine the experiences and perceptions of students when their classes pivoted from face-to-face to mediated, usually through video conferencing for synchronous or learning management systems for asynchronous. More specifically, we have collected qualitative data that addresses the communication students received from their instructors, what they believed instructors did successfully, what instructors could have done better, and the advice they would offer to instructors who found themselves in a similar crisis situation in the future.